Multidisciplinary monitoring of mud volcanoes: a new perspective on fluids and seismicity link from the Salse di Nirano (Italy) - E. Ferrari; A. L. Rizzo; G. Capelli Ghioldi; A. Sciarra; G. Tamburello; F. Viveiros; S. Lovati; M. Massa (Natural Hazards, 2026)
Understanding the relationship between fluids and seismicity is crucial for improving seismic hazard assessment, as fluid migration can play a significant role in earthquake triggering. Here, we present the results from an innovative real-time multiparametric monitoring implemented at the so-called ‘Salse di Nirano’ or mud volcano field (Northern Apennines, Italy), a region of medium to high seismic hazard. The objective is to investigate how geofluid dynamics relate to local seismicity. Two bubbling mud pools were selected for continuous monitoring of mud level, temperature, and electrical conductivity. Additionally, a CO 2 flux station was installed on the field’s edge, where elevated gas emissions are observed. Complementary meteorological and seismic stations track atmospheric conditions and seismic activity. Notably, anomalous shifts in mud pool electrical conductivity and soil CO 2 flux were recorded in temporal correlation with two distinct seismic swarms in 2024, highlighting the potential of fluid-geochemistry monitoring as a tool for tracking subsurface processes linked to seismic unrest.